Relationship between emotional intelligence and innovative work behaviors in Turkish banking sector - Dincer, Hasan; Orhan, Nazife (International journal of finance & banking studies, 2012)
Nowadays, almost all sectors especially service ones are aware of the fact that the presence of employees who have high level of emotional intelligence and innovative work behaviors is crucial so as to perform efficiently and productively. Since customer satisfaction and customer loyalty are the main primacy for the banking sector, they need to keep up with all kinds of changes and developments to resist and gain advantages over their competitors subject to the highly increase of competition worldwide.  The main reason of applying this study on the banking sector is its dynamic structure that has been changed both positively and negatively owing to the economic crisis. In connection with this, it is aimed to present the importance of emotional intelligence and innovative work behaviors on the success of banking sector through the analysis of two variables in terms of their relationship between each other. Additionally, it is intended for setting forth the differences of state-owned and private banks in terms of the level of emotional intelligence and innovative work behaviors. As a data collection tool, questionnaire technique has been used. It has been benefited from the emotional intelligence scale developed by Wong and Law to obtain the data related to emotional intelligence level; and the innovative work behaviors scale developed by Janssen to obtain the data related to innovative work behaviors. The findings obtained from the questionnaire were applied to 332 employees in Turkish banking sector.